Management practices of dedicated research nurses in an ophthalmic research hospital - LIANG Mengyin; LIANG Jiaen; ZHANG Enen; LIAO Ruilian; XIAO Huiming; HUANG Wenmin; LIU Yuhong (Yanke Xuebao)
Ophthalmic research hospitals serve as critical platforms for advancing medical innovation and translating research outcomes into practice. Dedicated Clinical Research Nurses (CRNs) play a pivotal role in enhancing the quality, compliance, and integrity of clinical research conducted within these settings. However, in China, there remains a lack of systematic models and practical guidance for CRN management specific to the field of ophthalmology, which has hindered the full realization of their professional value and the advancement of institutionalized development. This study examined CRN management practices at Zhongshan Ophthalmic Center, Sun Yat-sen University, a Grade A tertiary ophthalmic research hospital, between 2013 and 2024 as a case example to systematically examine the development pathway and outcomes of its CRN management system. The findings demonstrate that the implementation of a standardized system encompassing entry qualifications, tiered training, and structured practice models significantly enhanced both the professional competency of CRNs and the overall quality of clinical research projects. According to institutional quality control data, the quality score of clinical research projects increased significantly from 67.5±17.2 to 99.3±1.0 (P<0.001) following the integration of CRNs. Moreover, the study identifies three core functional domains of CRNs: (1) optimizing research processes to improve project coordination and efficiency; (2) managing research participants to safeguard ethical compliance and rights protection; and (3) ensuring data quality and integrity through rigorous oversight. In response to persistent challenges such as unclear role definitions, insufficient training systems, and lagging policy support, the study proposes actionable strategies, including the institutionalization of hierarchical and continuous training as well as the refinement of policy frameworks. These findings provide a scalable and evidence-based reference for promoting the professionalization and systemic development of ophthalmic clinical research nursing in China.